Identificação dos mecanismos envolvidos no relaxamento da musculatura lisa cavernosa e da aorta de coelho, induzido por doadores de óxido nítrico do complexo nitrosil-rutênio - Cerqueira, Joao Batista Gadelha de (2008)
Endothelial dysfunction makes 56% of patients with erectile dysfunction decline treatment with PDE-5 inhibitors. New forms of treatment are necessary for this group of patients. The present study evaluates the relaxation in vitro induced in rabbit corpus cavernosum smooth muscle and aortic rings by sodium nitroprusside (SNP) and by two new NO-donor substances of the nitrosyl-ruthenium complex: Rut-Byp and Rut-Caf. Tissues immersed in isolated baths of Krebs-Henseleit solution (37oC; pH 7.4) were precontracted with 1uM phenylephrine (PE). Relaxation concentration/response curves were plotted for all concentrations (10-12 to 10-4 M). To explore the mechanisms involved in induced relaxation, the following substances were added: 3µM, 10µM, 30µM or 100µM ODQ (soluble guanylate cyclase-specific inhibitor), 3µM or 10 µM oxyhemoglobin (extracellular NO scavenger), 1 mM L-cysteine (nitrosyl anion-specific scavenger), 100µM hydroxycobalamin (NO free radical scavenger), glibenclamide (ATP-dependent potassium channel blocker), iberiotoxin (medium and high-conductance potassium channel blocker) and apamin (low-conductance potassium channel blocker). The tissue samples were frozen in liquid nitrogen in order to quantify GMPc and AMPc produced during relaxation. All the substances tested produced a significant level of relaxation in the aortic vascular endothelium. Similar results were found for corpus cavernosum smooth muscle, with the exception of Rut-Byp (Emax 30%). In this tissue, Rut-Caf e SNP induced dose-dependent relaxation with a potency (pEC50) of 4.2 and 5.2, and a maximum effect (Emax) of 100% and 80%, respectively. All substances acted through the activation of soluble guanylate cyclase (sGC); therefore, the addition of 100µM ODQ inhibited the relaxation effect completely in all cases. Oxyhemoglobin reduced relaxation induced by all substances. At 3µM, the maximum effect (Emax) was reduced by 26% on the average, and at 10µM the effect was reduced by another 50% (p<0.05), though not completely neutralized. L-cysteine failed to affect relaxation, but hydroxycobalamin abolished Rut-Caf-induced relaxation in aortic rings (Emax: 112% vs 10%; p<0.005). A significant reduction was observed in corpus cavernosum smooth muscle relaxation, though not as intense as in aortic rings. The addition of glibenclamide to the baths increased the potency of Rut-Caf significantly (4.09 vs. 7.9; p<0.005) with no significant change in maximum effect. Potency and maximum effect remained unchanged with the other ion channel blockers. The agents released cGMP in both tissues studied. NO-donor substances of the nitrosyl-ruthenium complex were shown to be potent vasodilators. One substance (Rut-Caf) induced significant relaxation in animal corpus cavernosum. The substances tested in the study act through the activation of soluble guanylate cyclase producing intracellular GMPc. During relaxation they release NO and its free radical intracellularly, but not nitrosyl. They do not act directly upon potassium ion channels. Rut-Caf acts independently of the endothelial integrity.